Common Fixed Points of Generalized Rational Type Cocyclic Mappings in Multiplicative Metric Spaces. (9th July 2015) - Abbas, Mujahid; De la Sen, Manuel; Nazir, Talat
Abstract : The aim of this paper is to present fixed point result of mappings satisfying a generalized rational contractive condition in the setup of multiplicative metric spaces. As an application, we obtain a common fixed point of a pair of weakly compatible mappings. Some common fixed point results of pair of rational contractive types mappings involved in cocyclic representation of a nonempty subset of a multiplicative metric space are also obtained. Some examples are presented to support the results proved herein. Our results generalize and extend various results in the existing literature.